Juridical Analysis of The Application of Diversion in The Juvenile Criminal Justice System at The Investigation Level - Sahren, Hasbi; Harmono, Harmono; Sanusi, Sanusi (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to determine the legal regulation of diversion and identify obstacles and solutions in implementing diversion in the juvenile criminal justice system at the investigation level. The research method used is empirical juridical, with interviews as a primary data source and literature studies as a secondary data source. The results of the study show that crimes involving children in 2023 and 2024 in Majalengka are quite diverse, with the highest case being sexual intercourse, with a total of 20 cases. Obstacles in implementing diversion include requests for compensation that are difficult to fulfill, lack of understanding by law enforcement officials, and low public support. The proposed solutions include ongoing training for law enforcement officials and education to the public about the importance of diversion.